China and the world - British Broadcasting Corporation. Television Service (New York : Time-Life Multimedia, 1971)
Discusses the 19th century invasions and defeats of China by foreign powers. Explains the effect of the Japanese war and the seizure of Taiwan, Korea, and Manchuria, including China's reactions toward restored dignity in Korea and the deterioration of her relations with the Soviet Union.
Title from data sheet.
U standard.
Keywords: China -- Foreign relations